2010
DOI: 10.1287/mksc.1090.0512
|View full text |Cite
|
Sign up to set email alerts
|

The Price Precision Effect: Evidence from Laboratory and Market Data

Abstract: We examine two questions: Does the roundness or precision of prices bias magnitude judgments? If so, do these biased judgments affect buyer behavior? Results from five studies suggest that buyers underestimate the magnitudes of precise prices. We term this the precision effect. The first three studies are laboratory experiments designed to test the existence of the precision effect and examine the underlying psychological processes. In Study 1, we find that precise prices are judged to be smaller than round pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 25 publications
8
92
2
1
Order By: Relevance
“…A series of recent papers (Janiszewski and Uy, 2008;Thomas et al, 2010;Mason et al, 2013;Backus et al, 2015), though, provide evidence that in negotiations if the first offer (or listing price) is more precise (i.e., not round) that the other party appears to bargain less forcefully and outcomes are closer to the initial offer. Janiszewski and Uy propose that this effect arises because precise numbers trigger people to think in a finer classification scale and hence adjustment from an initial anchor happens over a tighter range of values.…”
Section: Experimental Evidence On Focal Points and Bargainingmentioning
confidence: 99%
“…A series of recent papers (Janiszewski and Uy, 2008;Thomas et al, 2010;Mason et al, 2013;Backus et al, 2015), though, provide evidence that in negotiations if the first offer (or listing price) is more precise (i.e., not round) that the other party appears to bargain less forcefully and outcomes are closer to the initial offer. Janiszewski and Uy propose that this effect arises because precise numbers trigger people to think in a finer classification scale and hence adjustment from an initial anchor happens over a tighter range of values.…”
Section: Experimental Evidence On Focal Points and Bargainingmentioning
confidence: 99%
“…The three experiments reported on here aimed at extending research on numerical precision as a confidence cue in a political-administrative setting (Janiszewski & Uy, 2008;Thomas et al, 2010;Mason et al, 2013;Jerez-Fernandez et al, 2014;Zhang & Schwarz, 2013). The precision effect runs counter to a core emphasis on the value of simplicity in numerical performance data which is found in performance management and measurement research (March & Simon 1956;Moynihan, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Some have suggested that politicians might benefit from inflating their stated confidence about numbers (Wildavsky, 1964;Radzevick & Moore, 2011). Recent research suggests that one way of increasing citizens' confidence in numbers is by using more precise numbers (Janiszewski & Uy, 2008;Thomas et al, 2010;Mason et al, 2013;Jerez-Fernandez et al, 2014;Zhang & Schwarz, 2013). For instance, Mason et al (2013) find that precise offers in negotiations are perceived as more informed which prompts less adjustment away from precise offers compared with round ones.…”
mentioning
confidence: 99%
“…Great care was taken to only use so-called "precise prices", e.g. 14.18 instead of 14.00, to circumvent potential precision effects [13] for which precise prices are practically handled as being of lower value than comparable round prices. To minimize confounding effects of different price level distributions among the ranges, the mean buying prices for each range was approximately set to the median for the referring range and the distribution of all ranges was normal.…”
Section: Methodsmentioning
confidence: 99%